Analysis of the features of economic relations of the European Union with the ASEAN (Association of Southeast Asian Nations) countries - Nycz-Wojtan, Sylwia (Technology audit and production reserves, 2018)
The object of research is the features of economic relations of the European Union and countries-members of the ASEAN (Association of Southeast Asian Nations) union. One of the most problematic places is that European Union as a supranational institution is currently experiencing a crisis, on various levels. From economic problems beginning, especially with the so-called PIGS countries (Portugal, Italy, Greece, and Spain), through difficulties in concluding internal political consensus and «speaking» with one voice on the international forum, ensuring security of Europe on the eastern border. In the process of research, general scientific and special methods of cognition were used: analysis of economic processes, generalization of analyzed features of economic cooperation of the European Union and countries-members of ASEAN. The structurally-functional method has allowed to highlight the main risks and areas of the program implementation strategy for cooperation with ASEAN members. The statistical method was used in assessing and analyzing the state of trade balance between the EU and ASEAN members. In the course of the research it was identified that in the resolution of political or security difficulties, the European Community mainly depends solely on its own strength. In terms of economic matters there are a number of regions with which this closer cooperation seems to be a logical solution that may bring benefits in the near future. One of them is Southeast Asia. As a result of the research it is shown that ASEAN has been a rapidly growing organization in the region for many years and its trade potential for EU is increasing rapidly. Strengthening international cooperation on the European Union – ASEAN line may prove to be a very important alternative for European economies. In addition, such an alliance may be the basis for a broad exchange of technological and educational experience, creating the nucleus of future strategic relations. The results of research shows not fully used potential with ASEAN members’ cooperation. Abilities and areas of future cooperation of EU companies particularly and EU countries in general could be the ground for future investigations with ASEAN members.